Noninvasive Stimulation of the Ventromedial Prefrontal Cortex Indicates Valence Ambiguity in Sad Compared to Happy and Fearful Face Processing - Winker, Constantin; Rehbein, Maimu A.; Sabatinelli, Dean; Dohn, Mira; Maitzen, Julius; Roesmann, Kati; Wolters, Carsten H.; Arolt, Volker; Junghoefer, Markus (Frontiers in Behavioral Neuroscience, 2019)
The ventromedial prefrontal cortex (vmPFC) is known to be specifically involved in the processing of stimuli with pleasant, rewarding meaning to the observer. By the use of non-invasive transcranial direct current stimulation (tDCS), it was previously possible to show evidence for this valence specificity and to modulate the impact of the vmPFC on emotional network processing. Prior results showed increased neural activation during pleasant relative to unpleasant stimulus processing after excitatory compared to inhibitory vmPFC-tDCS. As dysfunctional vmPFC activation patterns are associated with major depressive disorder (MDD), tDCS of this region could render an attractive application in future therapy. Here, we investigated vmPFC-tDCS effects on sad compared to happy face processing, as sad faces are often used in the study of mood disorders. After counterbalanced inhibitory or excitatory tDCS, respectively, healthy participants viewed happy and sad faces during magnetoencephalography (MEG) recording. In addition, tDCS effects on an interpretational bias of ambiguous happy-sad face morphs and an attentional bias of a dot-probe task with happy and sad faces as emotional primes were investigated. Finally, in conjoint analyses with data from a previous sibling study (happy and fearful faces) we examined whether excitatory vmPFC-tDCS would reveal a general increase in processing of pleasant stimuli independent of the type of unpleasant stimuli applied (sad vs. fearful faces). MEG and behavioral results showed that happy faces promoted a relative positivity bias after excitatory compared to inhibitory tDCS, visible in left orbitofrontal cortex and in the emotion-primed dot-probe task. A converse pattern in the MEG data during sad face processing suggests the possible involvement of an empathy network and thus significantly differed from neuronal processing of fearful face processing. Implications for the bearing of vmPFC modulation on emotional face processing and the impact of specific unpleasant face expressions are discussed.